Endothelial Cell Markers in Patients with Pseudoexfoliation Syndrome - Joanna Stafiej; Grażyna Malukiewicz; Hanna Lesiewska-Junk; Danuta Rość; Karolina Kaźmierczak (The Scientific World Journal)
The aim of the study was the assessment of the von Willebrand antigen (vWF Ag), E-selectin, and P-selectin concentration in blood plasma of patients with pseudoexfoliation syndrome (PEX). The group studied comprised 30 patients with PEX, aged from 50 to 86 years (mean 73, SD ± 8 years). Patients with cardiovascular and cerebrovascular diseases, diabetes mellitus, infectious disease, cancer, renal or liver insufficiency, connective tissue disease, current smoking, and hormone, antiplatelet, hypolipidemic, antioxidant, or antihypertensive drug therapy were excluded from the study. Each subject underwent a complete ophthalmological examination. Venous blood samples from the cubital vein were taken into sodium citrate solution. VWF Ag, sP-selectin, and sE-selectin concentration were determined by a commercially available enzyme-linked immunosorbent assay (MedSystems, Diagnostica Stago/Roche, R&D). Concentrations of vWF Ag, soluble E-selectin, and soluble P-selectin in blood plasma in the study group were compared with the levels in blood plasma in the control group. No significant differences were found between the groups. Our results indicate that there might be no correlation between PEX and such endothelial cell markers as vWF Ag, sP-selectin, and sE-selectin concentrations. Since the study size is limited, further investigations to confirm that there is no association between endothelial dysfunction in PEX and risk of future cardiovascular disease are necessary.